2017
DOI: 10.1016/j.sjbs.2017.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prevalence of hydatidosis in slaughtered Sawakny sheep in Riyadh city, Saudi Arabia

Abstract: Hydatidosis, or echincoccosis, is a serious medical and veterinary problem in many countries, particularly those with rural communities where there is a greater contact between dogs and domestic animals. Domestic livestock act as intermediate hosts which are the main reservoir for the disease in humans. It is therefore very important to estimate the prevalence of hydatid cysts in slaughtered animals since it can be transmitted to humans through dogs, which act as the final host for the disease. From this point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 20 publications
10
31
3
Order By: Relevance
“…Compared to other countries, we notice that our infestation rate is lower than the one recorded in Egypt by Osman et al (2014) (8.06%). However, our result is significantly higher than the one recorded by Almalki et al (2017)…”
Section: Prevalence Of Echinococcus Granulosus Infection In Sheepcontrasting
confidence: 85%
“…Compared to other countries, we notice that our infestation rate is lower than the one recorded in Egypt by Osman et al (2014) (8.06%). However, our result is significantly higher than the one recorded by Almalki et al (2017)…”
Section: Prevalence Of Echinococcus Granulosus Infection In Sheepcontrasting
confidence: 85%
“…The highest condemnation rate is observed in summer and autumn. In a recent study, the highest rate recorded was in winter and spring [8]. While in another study, the highest prevalence of hydatid cyst was in summer [15].…”
Section: Discussionmentioning
confidence: 85%
“…Resulting in that infection ratio in imported sheep and goats higher than a local one [7]. Another study showed the relationship between the rate of infection and the effect of seasons on a one year (2015-2016) among Sawakny sheep, in Riyadh city [8]. The winter was the highest rate of infection at 1.38%, while the summer was the lowest rate of infection at 0.67%.…”
Section: Introductionmentioning
confidence: 99%
“…Hydatidosis is a serious medical and veterinary problem in many countries, particularly those with rural communities (Almalki et al ., 2017). A number of factors have been found to influence the frequency and intensity of canine echinococcosis.…”
Section: Discussionmentioning
confidence: 99%